Novel Polyketide Synthase from Nectria haematococca - Graziani, Stephane (American Society for Microbiology, 2004)
We identified a polyketide synthase (PKS) gene, pksN, from a strain of Nectria haematococca by complementing a mutant unable to synthesize a red perithecial pigment. pksN encodes a 2,106-amino-acid polypeptide with conserved motifs characteristic of type I PKS enzymatic domains: β-ketoacyl synthase, acyltransferase, duplicated acyl carrier proteins, and thioesterase. The pksN product groups with the Aspergillus nidulans WA-type PKSs involved in conidial pigmentation and melanin, bikaverin, and aflatoxin biosynthetic pathways. Inactivation of pksN did not cause any visible change in fungal growth, asexual sporulation, or ascospore formation, suggesting that it is involved in a specific developmental function. We propose that pksN encodes a novel PKS required for the perithecial red pigment biosynthesis.